Ectopic release of GHRH and ACTH from an adenoid cystic carcinoma resulting in acromegaly and complicated by pituitary infarction. Issue 748 (February 1988) - Southgate, H. J.; Archbold, G. P.; el-Sayed, M. E.; Wright, J.; Marks, V.
Abstract : A 23 year old man presented with a tumour mass in the lung. Subsequent investigation showed ectopic secretion of adrenocorticotrophic hormone (ACTH) and growth hormone releasing hormone (GHRH) from an adenoid cystic carcinoma. The patient progressed to show the clinical effects of long term exposure to high blood levels of both growth hormone and cortisol. The case was complicated by pituitary infarction. The very high blood levels of ACTH, growth hormone (GH) and GHRH proved resistant to treatment with the somatostatin analogue, SMS 201-995, and a possible side effect of the drug is reported. To our knowledge this is the first reported case of ectopic hormone secretion by an adenoid cystic carcinoma.